Abnormal somatosensory temporal discrimination in Parkinson's disease: Pathophysiological correlates and role in motor control deficits. Issue 2 (February 2018) - Lee, Myung Sik; Lee, Myung Jun; Conte, Antonella; Berardelli, Alfredo
Highlights: Somatosensory temporal discrimination threshold (STDT) is abnormal in PD. Prolonged STDT in PD correlates with the degree of nigrostriatal dopamine loss. Prolonged STDT in PD generates incorrect signals for the execution and control of finger movements. Abstract: Objective: The somatosensory temporal discrimination threshold (STDT), defined as the shortest time interval required for two tactile stimuli to be perceived as separate, is longer in patients with Parkinson's disease (PD). In this review, we discuss STDT findings in healthy subjects and in PD patients and the relationship between altered STDT and motor disturbances. Methods: A search was conducted on PubMed for papers dealing with PD and temporal discrimination published from January 1990 to July 2017. Results: Abnormal STDT in PD correlates with disease duration, disease severity and degree of nigrostriatal dopamine loss, and responds to dopaminergic medication. In PD, a prolonged STDT does not correlate, or only marginally correlates, with clinically assessed bradykinesia of finger tapping. By contrast, a prolonged STDT correlates with the variability in amplitude and speed of finger tapping as assessed by means of neurophysiological techniques and may contribute to impaired finger dexterity in PD. Conclusions: We suggest that abnormal temporal processing of sensory information in PD generates incorrect signals for the execution and control of voluntary movements. Significance: This review sheds light on unsolved questions regarding the relationship between STDT alterations and motor disturbances in PD and proposes directions for future research on this topic.